Risk Factors of Green Tobacco Sickness on Tobacco Farmers in Jember Indonesia (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction. Green Tobacco Sickness (GTS) is a disease in the working population that is still not widelydisclosed. GTS characterized by the main symptoms of nausea, vomiting, dizziness, excessive sweating,and occurs when in contact with wet tobacco. This research purpose is to assess the factors associatedwith the incidence of GTS in tobacco farmers in Jember, Indonesia. Methods. The research design is casecontrol. Research variables are occupational factors and individual factors. Data analysis using binnerlogistic regression. Result and Discussion. The results stated that the variable influencing the case of GTSin tobacco farmers was the work period OR = 2,944, (CI 1,127-7,693) smoking status OR = 18,083 (CI6.815-47,984) dermatosis complaints OR = 3,876 (CI = 1,238-12,138) and nutritional status was assessedwith a BMI, OR = 2.643 (CI = 1.038-6.733). Farmers with a working period of working 18 years have a riskof 2,944 times GTS compared to farmers with a work period of <18 years. Farmers with smoking status havea risk of 18,083 times GTS compared to non-smoking farmers. Farmers who have dermatoses have a risk of1,355 times GTS compared to farmers who do not have complaints of dermatosis. Farmers with an abnormal(overweight) BMI have a risk of 2,643 times GTS compared to farmers with a normal BMI. Conclusion.Factors that influence the GTS are age, sex, smoking status, complaints of dermatosis, nutritional status, andyears of service. The findings of this study suggest that integrated promotive and preventive measures fromboth agricultural owners and first-rate health care providers need in the form of providing self-help to reducedirect contact with wet tobacco, healthy living behavior without smoking and maintaining nutritional status.